Academical inclusion of the visually impaired (2017)
In Colombia, most of the disabled population is constituted by the visually impaired. Access to undergraduate education represents a major problem to this population, as only 1% are able to culminate higher education. In the case of the visually impaired, they have to face various challenges when entering University, relating to mobility, non-accessible classes and the difficulty to access academic material. Specifically, to access academic material some difficulties have been identified in the process of obtaining different academic texts. This is due to a lack of autonomy, as they always have to ask for someone's help. Also, the process of scanning the text for its posterior lecture is difficult and slow. Additionally, not all the texts are available in an adequate digital format and can't be read by the screen reader known as JAWS. Nowadays, they exist a number of solutions that aim to help the visually impaired in their daily lives activities. Nevertheless, some of them are not accessible, because of their high costs and their lack of usability. For this reason, we desire to develop a tool that can allow the visually impaired population an easy access to different academic texts, in an autonomous way. In this way, they wouldn't depend on others and could organize their study time in a more efficient way. Additionally, we aim to generate a more inclusive environment in education, hoping that this will incentivize a higher proportion of visually impaired individuals to enter higher education and culminate their studies